Dekonstruksi Bomoh Dalam Ritual Bedekeh Suku Akit Di Rupat Bengkalis Provinsi Riau - ., Suroyo; A, Fatmahwati (Pustaka : Jurnal Ilmu-Ilmu Budaya; Vol 21 No 1 (2021), 2021)
Bedekeh is medical traditional treatment that is from the ancient treatment of ancestor that has been done by Akit People when they need treatment such as seek and seen the desease or illness from the body of someone. This ritual is contained mystics which they believe if there is relation with the curing that is helped by the spirit of ancestor Akit that is based of Akit people’s faith. Both Batin and Bomoh have a big role of Akit Tribes life cycles. The role of Batin in Akit Tribe is important because they not only keep the tradition culture of Akit exist, but also lead the Bedekeh ritual (as Bomoh Besar ). Nowadays, exsistent of Batin is not used by or important because Batin himself has been replaced by the Village Head of Hutan Panjang ( Kepala Desa ) that is not nesessary from Akit People. When there was Undang-Undang Desa (Village Laws), Batin had two roles, Kepala Desa (Village Head) and the leader of Bedekeh Ritual. In Akit People, Batin and Bomoh have certain social roles and cultural system of Akit. The Profession of Bomoh politically authoritative discourse of power. The Position of Bomoh attract the variety of interests as the legitimacy of power. That posistion is used to gain the position, respect, and power. Discourse of power or knowledge is Foucault’s Theory, about correlation between Discourse, power, and knowledge to become the aspect in power of Batin and Bomoh for Bedekeh ritual for Akit People.